ATIHAN PEMBUATAN TEPUNG MOCAF SEBAGAI PENGGANTI TEPUNG TERIGU DI KELOMPOK WANITA TANI ENGGAL MUKTI - Anak Agung Oka; Siti Suptihatin; Teguh Santoso; Lia Wijaya; Nur Indah Sari; Riswanto (LPPM UMRI, 2019)
Abstract Community service in Reno Basuki village, Rumbia, Central Lampung was focus to develop the group of farm women or KWT. KWT is one of the way to make a good effect on economics situation of society and also the way to solve the problems of national economics. The biggest comodity in KWT Enggal Mukti is cassava. Product from cassava can be a solution of Indonesian’s problem. One of the problem about economics in Indonesia is about the number of using wheat flour. As we know that wheat flour was produced by using wheat and Indonesia cannot produce it. So, the Indonesian’s goverments have a decision to import it from the other country. This situation is not good for Indonesia because it can make bad impact for Indonesia. The way to solve this condition is looking for the other kind of flour, and one of them is MOCAF (Modified Cassava Flour). Finally, the community service in KWT Enggal Mukti is training about ‘how to make mocaf’. Keywords: KWT, Training, Mocaf Abstrak Pengabdian kepada masyarakat yang dilaksanakan di kampung Reno Basuki, Rumbia, Lampung Tengah terfokus pada pengembangan kelompok wanita tani (KWT). KWT sebagai salah satu tonggak perubahan perekonomian keluarga menjadi sebuah jalan untuk memperbaiki perekonomian nasional. Komoditas yang melimpah di kawasan KWT Enggal Mukti adalah singkong. Pemanfaatan singkong menjadi sebuah jalan baru untuk menyelesaikan permasalahan perekonomian di Indonesia Permasalahan yang kini terjadi adalah adanya kecenderungan masyarakat Indonesia dalam menggunakan tepung gandum, baik dibuat dalam bentuk olahan gorengan, kue, atau yang lainnya. Akan tetapi, gandum bukanlah komoditas asli dari Indonesia sehingga pemenuhan gandum dilakukan dengan cara impor. Hal ini pastilah sangat berdampak pada perekonomian nasional. Oleh karena itu, pada pengabdian masyaraakt ini akan dilakukan pelatihan pembuatan mocaf (modified cassava flour) sebagai alternatif pengganti tepung terigu. Kata Kunci: KWT, Pelatihan, Mocaf